Functional consequences of morphological variation between locally adapted populations - Camarillo, Henry (Kansas State University, 2018)
Natural selection drives the evolution of traits to optimize organismal performance, but optimization of one aspect of performance can often influence other aspects of performance. Here, we asked how phenotypic variation between locally adapted fish populations affect locomotion and ventilation, testing for functional trade-offs as well as trait-performance correlations. Specifically, we investigated two populations of livebearing fish (Poecilia mexicana) that inhabit distinct habitat types (hydrogen-sulfide-rich springs and adjacent nonsulfidic streams). For each individual fish, we quantified different metrics of burst-start swimming during simulated predator attacks, steady swimming, as well as gill ventilation. Coinciding with theoretical predictions, we documented significant population differences in all aspects of performance, with fish from sulfidic habitats exhibiting higher steady swimming performance and higher ventilation capacity but slower burst-starts. There was a significant functional trade-off between steady and burst-speed swimming, but not between different aspects of locomotion and ventilation, indicating modularity of traits associated with either aspect of function. While our findings about population differences in locomotion performance largely parallel the results from previous studies, we provide novel insights about how morphological variation might impact ventilation and ultimately oxygen acquisition. Overall, our analyses provided insights into the functional consequences of previously documented phenotypic variation, which will help to disentangle the effects of different sources of selection that may coincide along complex environmental gradients.
Keywords: adaptation; fish; functional morphology